DETERMINANTS OF TOTAL FACTOR PRODUCTIVITY ACROSS PHILIPPINE MANUFACTURING FIRMS: A SIMULTANEOUS QUANTILE REGRESSION ANALYSIS - Zandro Catacutan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Numerous studies found mixed evidence on the effects of firm-related factors toward the conditional distribution of TFP performance done in a cross-country, industry, and firm-level perspectives abroad. Unfortunately, there is still relatively little evidence to support these findings in the context of the Philippines. Thus, this study analyzed whether the conditional distribution of firm-level TFP performance varies according to the size of the firms, and forms of ownership, and examined the impact of firm-related factors such as firm size, form of ownership, R&D intensity, capital intensity, and export intensity on the conditional distribution of manufacturing firms’ TFP performance. The study utilized the comprehensive firm-level data gathered from the World Bank Enterprise Survey conducted in 2015 across selected manufacturing firms in the Philippines, and incorporated ordinary least squares regression and simultaneous quantile regression models in the estimation analyses. Empirical findings revealed that the conditional distribution of firm-level TFP performance marginally varies across selected manufacturing firms while these firms solely focus on domestic operations supported by capital outlays with less engagement in R&D activities. Lastly, capital intensity and firms’ form of ownership were found to have statistically significant effects on the conditional distribution of firm-level TFP performance observed across all quantiles.